On decoloniality : concepts, analytics, praxis / Walter D. Mignolo and Catherine E. Walsh. - Mignolo, Walter; Walsh, Catherine E. (Duke University Press, 2018)
In 'On Decoloniality' Walter D. Mignolo and Catherine E. Walsh explore the hidden forces of the colonial matrix of power, its origination, transformation, and current presence, while asking the crucial questions of decoloniality's how, what, why, with whom, and what for. Interweaving theory-praxis with local histories and perspectives of struggle, they illustrate the conceptual and analytic dynamism of decolonial ways of living and thinking, as well as the creative force of resistance and re-existence. This book speaks to the urgency of these times, encourages delinkings from the colonial matrix of power and its 'universals' of Western modernity and global capitalism, and engages with arguments and struggles for dignity and life against death, destruction, and civilizational despair.